1996
DOI: 10.1016/0014-5793(96)00741-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for bidirectional histamine transport by murine hematopoietic progenitor cells

Abstract: Murine hematopoietic progenitor cells synthesize substantial amounts of histamine in response to IL-3 or calcium ionophore. They also take up extracellular histamine by an active transport system. In the present study we demonstrate that this system mediates both influx and efflux of histamine. Indeed, MR16155 and thioperamide, the two 1-13 antagonists which are most effective in inhibiting histamine uptake, likewise diminish the release of preloaded histamine from bone marrow cells. These compounds also inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Other mediators of DMH histamine uptake may include the newly described plasma membrane monoamine transporter (Engel et al, 2004), which is relatively insensitive to corticosterone (K i ϭ 450 M) and the H3 histamine receptor (Corbel and Dy, 1996). In contrast to its effect on histamine uptake, corticosterone was less efficacious at inhibiting MPP ϩ uptake than was D22 (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Other mediators of DMH histamine uptake may include the newly described plasma membrane monoamine transporter (Engel et al, 2004), which is relatively insensitive to corticosterone (K i ϭ 450 M) and the H3 histamine receptor (Corbel and Dy, 1996). In contrast to its effect on histamine uptake, corticosterone was less efficacious at inhibiting MPP ϩ uptake than was D22 (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Huszti et al [8][9][10] showed that histamine uptake by astroglial and cerebral endothelial cells represented a carrier-mediated, energy-and sodium-dependent highaffinity mechanism, which was definitely involved in the inactivation and clearance of neuronal histamine. It was also established that hematopoietic progenitor cells from murine bone marrow had the capacity to take up considerable amounts of extracellular histamine, which accumulated inside the cells [2] . This histamine transport is partially dependent on the presence of an electrochemical Na + gradient such as astrocytes and endothelial cells [8][9][10] and it is temperature-dependent as well.…”
mentioning
confidence: 99%
“…This histamine transport is partially dependent on the presence of an electrochemical Na + gradient such as astrocytes and endothelial cells [8][9][10] and it is temperature-dependent as well. The hematopoietic progenitors also possessed a histamine transport system with bidirectional functions, the inward and outward currents [2] . Recently, we reported that the characteristics of [ 3 H]histamine uptake into bone marrowderived cells from L -histidine decarboxylase gene knockout mice [17] .…”
mentioning
confidence: 99%
“…As shown in Fig. 2 bi-directional [14], we examined whether the compounds that blocked histamine uptake also inhibited its release from IL-3-induced BMC. We found that in the presence of iodoproxyfan, carboperamide, FUB 181 or FUB 130 at optimal concentration (10 \iM), bone marrow supernatants contained about 60% less histamine than controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the blockade of histamine uptake also inhibits the release of newly synthesized, IL-3-induced histamine from BMC, while intracellular histamine levels increase. II-3-dependent cell lines composed of immature myeloid cells arrested at a particular stage of the differentiation scheme have a similar transport system [14].…”
Section: Introductionmentioning
confidence: 99%